2015
DOI: 10.1016/j.proeng.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Observation of Elementary Transition Boiling Process after Sudden Contact of Liquid with Hot Surface

Abstract: A Fast response surface temperature measurement technique has been developed to investigate transient transition boiling phenomena after ethanol droplet impact on a nickel hot surface. Our motivation is to make clear the mechanism of boiling transition between nucleate and film boiling which is closely related the recovery of wetting on the hot surface being higher than the Leidenfrost temperature. In this study transient boiling phenomena during sudden contact of an ethanol sessile droplet on a hot solid surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The drop test experiment and its results is important in thermal engineering application such as power plant [9]- [10], material manufacturing process [11], thermal energy and cooling studies [12]- [14], quenching and spray cooling studies [15]- [17] and many others. Drop impact researcher such as Moita and Moreira [18], Illias et al [19]- [26], Mitsutake et al [27]- [28], Inada et al [29]- [30] and many other uses a single drop test in their experimental work. Drop test experiment can be used to study the behavior of impacting droplets, evaporation characteristic, vapor film generation, heat flux analysis and many others.…”
Section: Introductionmentioning
confidence: 99%
“…The drop test experiment and its results is important in thermal engineering application such as power plant [9]- [10], material manufacturing process [11], thermal energy and cooling studies [12]- [14], quenching and spray cooling studies [15]- [17] and many others. Drop impact researcher such as Moita and Moreira [18], Illias et al [19]- [26], Mitsutake et al [27]- [28], Inada et al [29]- [30] and many other uses a single drop test in their experimental work. Drop test experiment can be used to study the behavior of impacting droplets, evaporation characteristic, vapor film generation, heat flux analysis and many others.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the Leidenfrost temperature, it is possible to enhance the cooling performance and heat absorption capabilities of materials and liquids. Numerous researchers have conducted detailed studies on droplet behaviour by utilizing high-speed video cameras, investigating critical parameters such as droplet shape, maximum spreading, contact angle, droplet size, wetting behaviour, evaporation time, boundary conditions, and boiling explosion, among others [13][14][15][16][17][18][19][20][21][22][23][24]. These studies contribute to the understanding of droplet impact in boiling heat transfer processes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that neither the existing capillary regime nor viscous regime identified for droplet impacts on impermeable surfaces (or a combination of these regimes) could describe β max for droplet impact on a porous surface over a wide range of We. Other researchers such as Illias et al [16][17][18][19][20][21], Rosman et al [22], Mitsutake et al [23], Tsuboyama et al [24] and Hasan et al [25][26] also conducted a few experimental works regarding droplet impact research in order to improve the understanding regarding the relationship between droplet impact and hot surfaces. In this paper, we focus our investigation in finding the Critical Heat Flux (CHF) by using three (3) different types of material.…”
Section: Introductionmentioning
confidence: 99%